Effects of low-energy ion beam bombardment on biological cell envelopes - L. D. Yu (2018)
Low-energy ion beam biotechnology has seen rapid development worldwide in recent years. This is an important expansion of studies on ion beam modification of solid materials, vastly different from and more complex than the latter. Among other novelties, we have focused our interest on ion beam bombardment effects on plant and bacterial cell envelopes and tried to understand mechanisms involved in ion beam-induced gene transfer. Through a comprehensive investigation, we have discovered ion beam-induced formation of nanocrater-like structures in the cell envelope, a general phenomenon of ion beam bombardment of cells; these structures may act as pathways for exogenous macromolecule transfer. We have also quantitatively obtained abnormally great penetration depth and sputtering of ions in the cell envelope. All these results are significantly advantageous for ion beam processing of biological cells. © 2007 Elsevier B.V. All rights reserved.